Association between electromyographic localized muscle fatigue of the rectus femoris and static postural balance in physically active adult men - Mariam Mian Bouchnak; Thatiane Lopes Valentim Di Paschoale Ostolin; Evandro Fornias Sperandio; Wesley de Oliveira Vieira; Victor Zuniga Dourado (Universidade Federal de Santa Catarina, 2020)
Although the determinant impact of exercise-induced muscle fatigue prior to postural balance assessment has been widely described, recent evidence suggests that hyperventilation and sensorimotor losses, rather than muscle fatigue, are responsible for the changes observed in postural balance. However, the association between localized muscle fatigue (LMF), induced by isokinetic dynamometer protocol test and assessed through surface electromyography, and postural balance in adults is poorly understood. We aimed to evaluate the association between the LMF of the rectus femoris and static postural balance in 51 adult men (43±14.8 years; 26.9±5 kg/m2). We obtained physical activity level and postural balance, respectively, through a triaxial accelerometry and a force platform. The quadriceps femoris strength and endurance were obtained using an isokinetic dynamometer and surface electromyography simultaneously. The association between the isokinetic and electromyographic LMF and static postural balance was investigated using linear regression models adjusted for age, body mass index, and isokinetic quadriceps strength and LMF. The correlations between postural balance variables and isokinetic muscle strength and LMF were weak-to-moderate. After multivariate analyses, we observed that electromyographic LMF were a predictor of postural balance, mainly of the mean amplitude and COP area and velocity in the mediolateral direction, regardless of isokinetic variables. Therefore, LMF plays a determinant role in the postural balance of physically active adult men. Fatigue indices are significant predictors of postural balance, regardless of previous fatigue induction.